Antimicrobial and Antifungal Activity of Mn(III) Complexes of 2,5-Dihydroxy-3-undecyl-1,4-benzoquinone Derivative - SUSHAMA, P.G.; MARY DOROTHY, A.; ALAUDEEN, M. (Asian Journal of Chemistry, 2010)
Structural modifications of embelin (2,5-dihydroxy-3-undecyl-1,4-benzoquinone), a bioactive compound, were attempted earlier to get various pharmacological profiles. In view of the above reports a new azo derivative of 2,5 dihydroxy-3-undecyl-1,4-benzoquinone with 2-aminobenzothiazole was prepared. The product 6-(2'-benzothiazolylazo) embelin was complexed with Mn(III) chloride, acetate, nitrate and perchlorate. The complexes were screened for antibacterial, antifungal and anthelmintic activities and the complexes were found to exhibit enhanced activity than the ligand.